PARTISIPASI MASYARAKAT DALAM KEGIATAN SISKAMLING DI PERUMAHAN GRIYA SAVANA SUKARAMAI DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - ", Misbakhudin; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in residential Griya Savana Sukaramai Desa Tarai Bangun Kecamatan Tambang Kabupaten Kampar. With the aim to know the community participation in siskamling activities in housing Griya Savana Sukaramai. The problem in this research is 1. How the level of community participation in siskamling activities in housing Griya Savana Sukaramai 2. What factors influence the community participation in siskamling activities in housing Griya Savana Sukaramai. This research is a descriptive quantitative research. As for the population in this study is the residential community Griya Savana Sukaramai who do siskamling. Because the number of people who carry out siskamling activities have been know then in this study the author in the sampling technique used is the census. For data collection of researchers using interview methods, documentation and questionnaires. Data analysis of research result used quantitative analysis and in the writing described descriptively. Base on the result of the study can be concluded that community participation in siskamling activities is still high because most people are very active in activities siskamling. Factors influencing community participation in siskamling activities are the factors of awareness and willingness, age and work.Keywords : Participation, Siskamling, Tambang, Kampar